2017
DOI: 10.1093/europace/eux109
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of different ablation strategies for ventricular tachycardia in patients with structural heart disease: systematic review and meta-analysis

Abstract: In patients with SHD who had VT related mainly to ischaemic substrates, there was a significantly lower risk of the composite primary outcome of long-term VA recurrence and all-cause mortality among those undergoing substrate modification compared to standard ablation. Long-term success is improved when performing complete substrate modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 20 publications
5
60
2
Order By: Relevance
“…A statistically significant decrease in the composite endpoint of VT recurrence/all‐cause mortality associated with substrate modification as compared with standard ablation of stable VTs (risk ratio [RR] 0.57, 95% confidence interval [CI] 0.40–0.81) was found. Patients with complete substrate modification (defined as elimination of all late or fractionated potentials) had a decreased VT recurrence as compared to patients with incomplete substrate modification (RR 0.39, 95% CI 0.27–0.58) . In addition to the detected improved arrhythmia‐free survival, which is in accordance with previously available evidence, the meta‐analysis provides novel evidence suggesting a mortality benefit in patients undergoing substrate‐based ablation …”
supporting
confidence: 84%
See 2 more Smart Citations
“…A statistically significant decrease in the composite endpoint of VT recurrence/all‐cause mortality associated with substrate modification as compared with standard ablation of stable VTs (risk ratio [RR] 0.57, 95% confidence interval [CI] 0.40–0.81) was found. Patients with complete substrate modification (defined as elimination of all late or fractionated potentials) had a decreased VT recurrence as compared to patients with incomplete substrate modification (RR 0.39, 95% CI 0.27–0.58) . In addition to the detected improved arrhythmia‐free survival, which is in accordance with previously available evidence, the meta‐analysis provides novel evidence suggesting a mortality benefit in patients undergoing substrate‐based ablation …”
supporting
confidence: 84%
“…Additionally, recent evidence implies that VT induction and mapping before substrate ablation only prolongs the procedure, radiation exposure, and the need for electrical cardioversion without increasing acute and long-term ablation outcomes, when compared with substrate ablation as the first step. We conducted a meta-analysis comparing substrate-based versus standard ablation of VT. 14 15 There was no significant difference in age or ejection fraction between the groups. Procedure times were longer for the PVAD group and there was no difference in inducibility at the end of the procedure between the PVAD and non-PVAD group (77 vs. 67%, P = 0.69).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…As such ablation is recommended by multiple guidelines for the management of drug‐refractory ventricular arrhythmias . Mirroring such recommendations, there has been a large growth of VT ablations worldwide . Whether similar trends are seen in Australia remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…11 Mirroring such recommendations, there has been a large growth of VT ablations worldwide. [12][13][14][15][16] Whether similar trends are seen in Australia remains unknown. We have previously shown that catheter ablation of atrial fibrillation (AF), the most common cardiac arrhythmia in humans, has grown at an exponential rate, at up to 39.8% per year, when compared to other common interventional cardiovascular procedures, such as percutaneous coronary intervention (PCI).…”
mentioning
confidence: 99%